ChemInform Abstract: General Allylic C—H Alkylation with Tertiary Nucleophiles. Issue 42 (14th October 2014) - Howell, Jennifer M.; Liu, Wei; Young, Andrew J.; White, M. Christina
Abstract A general method for intermolecular allylic C—H alkylation of terminal olefins with tertiary nucleophiles is developed employing palladium(II)/bis(sulfoxide) catalysis.